; Institutional Factors Influencing Political Trust in Modern Russia - Marina Yu. Malkina; Vyacheslav N. Ovchinnikov; Konstantin A. Kholodilin (Journal of Institutional Studes, 2020)
– (, ) . . () « / , » (LiTS – Life in Transition Survey). , . . . . -, , 2016 . () . -, , , . -, . . – – The aim of this study is to analyze and assess the impact of institutional factors on political trust in various levels of government (federal, regional and local) in modern Russia. Data and methods. The study is based on microdata from the European Bank for Reconstruction and Development (EBRD) “Life in Transition Survey” (LiTS). We examined such institutional factors of political trust as perceived government performance and level of corruption, as well as the level of interpersonal trust. The subjective decile of household wealth was an additional explanatory variable in our analysis. We estimated the model parameters using linear regressions with instrumental variables. Results and their application. First, we found that in 2016 the perceived effectiveness of the federal government was the main determinant of Russian trust in the president. At the same time, the perceived level of local corruption was a major factor of Russian citizens' (mis)trust in local authorities. Second, we found that poor households turned out to be the most loyal groups of the population towards the Russian president, and we explained this phenomenon by the active redistributive policy of the federal authorities. Third, we revealed a significant positive relationship between political and interpersonal trust at the micro level. In conclusion, we made recommendations on the effective management of political trust in modern Russia.
Keywords: 330; Political trust; Levels of authority; Institutional factors; Perceived level of corruption; Government effectiveness; Interpersonal trust; Subjective decile of wealth